1982
DOI: 10.1007/bf00156113
|View full text |Cite
|
Sign up to set email alerts
|

The wavelength variation of the granule/intergranule contrast

Abstract: Modern measurements of the granule contrast are reviewed and compared with a curve showing the wavelength variation to be expected on the assumption of black-body emission as well as with the predictions of recent inhomogeneous models. The difference in effective temperature between granules and intergranular lanes is ~270-280 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…So far no neutrino or cosmic-ray events were detected by any of these experiments. Given their sensitivity this is consistent with expectations from traditional air-shower arrays and has been used to set limits for the neutrino and cosmic-ray flux at ZeV energies [3].…”
Section: Radio Observation Of the Moonsupporting
confidence: 69%
“…So far no neutrino or cosmic-ray events were detected by any of these experiments. Given their sensitivity this is consistent with expectations from traditional air-shower arrays and has been used to set limits for the neutrino and cosmic-ray flux at ZeV energies [3].…”
Section: Radio Observation Of the Moonsupporting
confidence: 69%
“…CODALEMA [59], TREND [33], AERA [60], and ARIANNA [38] have shown that autonomous radio detection is feasible, but there remain some open questions: it has to be shown that the trigger can be pure and efficient enough for inclined showers, and there are technical challenges regarding infrastructure, data communication, and reliability of long-term and large-scale remote operation. Alternative ways to large apertures might be provided by observing air-showers with antennas in space [61], or by using the moon as a target [62]. However, these methods require successful proof-of-principle demonstrations, and it is not yet clear how they will compare in terms of measurement accuracy to ground-based antenna arrays.…”
Section: Applications Of the Radio Technique For Air Showersmentioning
confidence: 99%
“…Limits on the fluxes of ultra-high-energy cosmic rays (left) and neutrinos (right) set by the NuMoon [14], RESUN [15] and LUNASKA Parkes [17] lunar Askaryan experiments, calculated as described in the text. Also shown are potential limits that could be set by future lunar Askaryan experiments with nominal observing times of 200 h with LOFAR [20,25], 200 h with a phased-array feed (PAF) on the Parkes radio telescope [26], or 2900 h with AuScope [18]. Shading shows the range of uncertainty associated with models of the small-scale lunar surface roughness; the discontinuity is an artefact of the model.…”
Section: Dedispersionmentioning
confidence: 99%
“…I estimate the limits or potential limits set by some past and near-future lunar Askaryan experiments using an analytic model for the particle aperture [18,23,24]. To reflect the effects of small-scale surface roughness, I use the only extant model [13], which represents the aperture as a linear combination of two extreme cases: one in which these effects are ignored, and one in which they are maximised, by representing the surface as a series of small-scale facets with uncorrelated slopes.…”
Section: Particle Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation